Accuracy of four commercial systems for identification of Burkholderia cepacia and other gram-negative nonfermenting bacilli recovered from patients with cystic fibrosis. - Kiska, D L (1996)
Burkholderia cepacia has recently been recognized as an important pathogen in chronic lung disease in patients with cystic fibrosis (CF). Because of the social, psychological, and medical implications of the isolation of B. cepacia from CF patients, accurate identification of this organism is essential. We compared the accuracies of four commercial systems developed for the identification of nonfermenting, gram-negative bacilli with that of conventional biochemical testing for 150 nonfermenters including 58 isolates of B. cepacia recovered from respiratory secretions from CF patients. The accuracies of the four systems for identifying all nonfermenters ranged from 57 to 80%, with the RapID NF Plus system being most accurate. The accuracies of these systems for identifying B. cepacia ranged from 43 to 86%, with the Remel system being most accurate. Depending on the commercial system, from two to seven isolates were misidentified as B. cepacia. The relatively poor performance of the commercial systems requires that identification of certain nonfermenters be confirmed by conventional biochemical testing. These organisms include B. cepacia, Burkholderia sp. other than B. cepacia, and infrequently encountered environmental species (Pseudomonas and Flavobacterium species). In addition, conventional biochemical testing should be done if a commercial system fails to assign an identification to an organism. Confirmatory testing should preferably be performed by a reference laboratory with experience in working organisms isolated from CF patients.